Young and out: An application of a prospects-based concept of social exclusion - Oddbjørn Raaum; Jon Rogstad; Knut Røed; Lars Westlie (University of Oslo, Department of Economics, 2005)
We develop a forward-looking empirical concept of social exclusion based on the estimated transition probabilities from a random effects multinominal logit-model. Youths are considered socially excluded if they are currently outside school/work and have a low predicted probability of re-entering in the near future. Implemented on extraordinary rich event history data of compulsory school graduates, we estimate social exclusion among Norwegian youths and find that social exclusion is (i) non-cyclical; (ii) rare among teen-agers, except for immigrant children and individuals with a disadvantaged family background; (iii) more prevalent among young adults in their early twenties; and (iv) independent of gender.
Keywords: I29; 330; social exclusion; multinominal logit-model; Youths; Soziale Isolation; Jugendliche; Logit-Modell; Schätzung; Norwegen